The influence of Jose da Silva Lisboa's journalism on the independence of Brazil (1821-1822) - CELESTINO, GUILHERME (Anthem Brazilian Studies., 2022)
This work analyses the influence of the publications from 1821-1822 written by José da Silva Lisboa, the future Viscount of Cairu, on the events that led to the independence of Brazil in 1822.